Transient oxygenation of the Mediterranean after the Zanclean megaflood - Udara Amarathunga; Jochen J. Brocks; Paul Th. Meijer; Janet M. Hope; Willem-Jan Zachariasse; Rick Hennekam; Isabel van der Hoeven; Ursula Roehl; Susan Rule; Ulrike Troitzsch; Simon Haberle; Appy Sluijs; et al. (Proceedings of the National Academy of Sciences, 2025)
The Mediterranean basin reconnected to the Atlantic Ocean ~5.33 Myr ago, following its partial desiccation during the preceding Messinian salinity crisis (5.97 to 5.33 Myr). While the extent of terminal Messinian drawdown and abruptness of reconnection are debated, recent work inferred that an anomalously long-lasting eastern Mediterranean organic-rich “mystery sapropel” layer was deposited due to salinity-stratification and anoxia following catastrophic flooding that refilled the basin. However, independent evidence is required to test this hypothesis. Here, we present extensive proxy data and numerical model results to show that irrespective of the largely hypersaline or oligohaline conditions proposed for the terminal Messinian, the eastern Mediterranean became oxygenated due to the ~1.5-km-high, turbulent and aerated cascade that refilled the basin, which created a salinity-stratified but oxygenated water column that allowed preservation of only the most recalcitrant organic components. Next, oxygen was gradually depleted over a period of up to 12,000 y due to remineralization of sinking organic matter, culminating in a stratified, anoxic basin. It took 33,000 y after flooding (7,000 y longer than suggested previously) for turbulent diffusion to weaken the stratification and allow resumption of convective deep-water renewal, which marked the final return of normal oxygenated marine conditions throughout the Mediterranean.